Untersuchungen zur Phosphataufnahme von Zwischenfrüchten bei unterschiedlicher P-Versorgung des Bodens (Investigation of P Uptake of Catch Crops under Different P Supply) - Eichler, Bettina; Grüner, Adolf; Vágó, Imre (Acta Agraria Debreceniensis, 2003)
The P uptakes of 11 different catch crops on four soils were estimated and compared with changes of double lactate soluble Phosphorus (P(DL)) in soil within a vessel trial. Additionally a model trial with quartz sand was carried out for investigations of the influence of P supply on root parameters. The differences of P uptake in dependence of the proofed variants were significant. Under a sufficient P supply Buckwheat, Maize and Oil radish had the highest P uptake on sandy soils, on loamy soil also Buckwheat and Maize but Serradella too. Under P deficiency the withdrawals of Phosphorus for Buckwheat, Maize and Oil radish were found to be the highest. In contrast to the sandy soils for the loamy soils no significant relation between the P uptake by plants and changes in the P-DL amount in soil could be found. For all variants the P uptake by plants were higher than the reduction of the P-DL amount in soil. The rate of P-DL content on the total P content in soil reduced while the two trial years only in sandy but not in loamy soils. The P uptake, the root length and the root/shoot relationship depends significantly on the cultivated crop and the added P compound. The added water soluble KH2PO4 caused a higher P uptake but a lower root/shoot-relationship than the water insoluble P compounds.